Inovasi Kurikulum Pendidikan Calon Guru Pendidikan Agama Islam - Soeparwati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article aims to reveal an innovative form of educational curriculum for prospective PAI teachers. This research method uses qualitative research through literature study with content analysis. The results of the study show that the Islamic Religious Education curriculum innovations as proclaimed by the Government and implemented by LPTKs include innovations to the Islamic Religious Education curriculum in Madrasas/Schools and Professional Education Program curriculum innovations. The innovation of the education curriculum for prospective PAI teachers in the PPG program manifests itself in the enrichment of pedagogic materials, enrichment of PAI teaching materials, mastery of learning tools and their implementation, and the ability to carry out classroom action research as a means of increasing teacher competence. Theoretically, the education curriculum for prospective PAI teachers is very comprehensive.